Usability of self-reported assessment of work functioning in municipal occupational rehabilitation teams: A qualitative study - Anne-Mette Hedeager Momsen; Merete Tonnesen; Birgitte Zwicky-Hauschild; Claus Vinther Nielsen; Claus Vinther Nielsen; Claus Vinther Nielsen; Reuben Escorpizo; Reuben Escorpizo; Vivian Langagergaard; Christina Malmose Stapelfeldt (Frontiers Media S.A., 2023)
AimsThis study aimed to explore (1) whether self-reported assessment on work-related functioning, workability, return-to-work (RTW) self-efficacy, and expectation was useful in the professionals' assessment of sick-listed workers and could guide referral to interventions and (2) whether self-reporting in addition to "usual practice" could improve the RTW dialog and involvement in case management.MethodsThe qualitative study took place in two municipal job centers in 2021. The assessment was based on the Work Rehabilitation Questionnaire, RTW-Self-efficacy Scale-19, and single items of self-rated health, workability, and RTW expectations. Sick-listed workers (n = 36) were interviewed by telephone. Three focus-group interviews were conducted with professionals who had used the questionnaire. Data were coded and analyzed thematically.ResultsThree themes with seven subthemes emerged: (1) accessibility; (2) one tool in the RTW toolbox (subthemes: a supplementary tool, a tool for reflection, facilitating interdisciplinary communication, and enhancing active participation); and (3) the value of "ticking boxes" (subthemes: good days, bad days, the issue of power, and the cultural meaning of words).ConclusionThe professionals would not recommend the present questionnaire for use during their rehabilitation team meeting for assessment, interdisciplinary communication, or choice of interventions. However, using the parts assessing RTW self-efficacy and expectation combined with a dialog may be of value early in the RTW process. The self-reporting assessment tool was perceived to be meaningful to some sick-listed workers, as it provided reflections on important aspects of the RTW process. Some workers believed that it might contribute to the rehabilitation team, and thus, it could improve their involvement.